2016
DOI: 10.1016/j.molcel.2016.08.010
|View full text |Cite
|
Sign up to set email alerts
|

A G-Rich Motif in the lncRNA Braveheart Interacts with a Zinc-Finger Transcription Factor to Specify the Cardiovascular Lineage

Abstract: Long non-coding RNAs (lncRNAs) are an emerging class of transcripts that can modulate gene expression; however, their mechanisms of action remain poorly understood. Here, we experimentally determine the secondary structure of Braveheart (Bvht) using chemical probing methods and show that this ∼590 nt transcript has a modular fold. Using CRISPR/Cas9-mediated editing of mouse embryonic stem cells, we find that deletion of 11 nt in a 5' asymmetric G-rich internal loop (AGIL) of Bvht (bvht) dramatically impairs ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
134
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(139 citation statements)
references
References 80 publications
2
134
0
Order By: Relevance
“…Recently, some studies have suggested long non-coding RNAs (lncRNAs) in cardiovascular physiology and the initiation and progression of cardiovascular disease (6)(7)(8). Early on in our study, we tested what genes were regulated by lncRNA260 by high throughput RNA and lncRNA chips screening and found that only the IL28RA gene was the only gene to be regulated by lncRNA260.…”
Section: Introductionmentioning
confidence: 92%
“…Recently, some studies have suggested long non-coding RNAs (lncRNAs) in cardiovascular physiology and the initiation and progression of cardiovascular disease (6)(7)(8). Early on in our study, we tested what genes were regulated by lncRNA260 by high throughput RNA and lncRNA chips screening and found that only the IL28RA gene was the only gene to be regulated by lncRNA260.…”
Section: Introductionmentioning
confidence: 92%
“…4 Notably, they found that a small deletion of 11 nt in the 5’ asymmetric G-rich internal loop motif in the modular secondary structure of Bvht using CRISPR/Cas9-mediated HR in mouse embryonic stem cells prevented its interaction with its binding partner CNBP. In order to increase efficiency of the mutation at designated locus at both alleles, two templates including different selection markers (i.e.…”
Section: Advantages and Disadvantages Of Lncrna Genome Editing Stratementioning
confidence: 99%
“…1B). 4 While this strategy has the advantage of understanding structure-function relationships of small domains of lncRNAs, the prediction tools for identifying such small structural domains are fairly nascent and require careful interpretation, often necessitating complementary mutational approaches to map such domains.…”
Section: Advantages and Disadvantages Of Lncrna Genome Editing Stratementioning
confidence: 99%
“…in the form of a cell-based biological pacemaker that, in the future, could replace electronic pacemaker devices. In keeping with the cardiac theme, Laurie Boyer (Massachusetts Institute of Technology, Cambridge, MA, USA) presented her group's work in determining the secondary structure of a long non-coding (lnc) RNA called Braveheart (Bvht) that is necessary for cardiac differentiation of mouse ESCs (Xue et al, 2016). Targeted disruption of a small G-rich internal loop (AGIL) motif of this lncRNA impaired cardiomyocyte differentiation and interaction with cellular nucleic acid-binding protein (CNBP, also known as ZNF9), a zinc-finger protein whose deletion partially rescued the Bvht mutant phenotype.…”
Section: Cardiac and Musculoskeletal Developmentmentioning
confidence: 99%